(untitled) (Journal of the College of Basic Education, 2022)
The difference in teaching methods in the Elements of Art subject and the lack of interest of teachers in the principle of individual differences and the adoption of traditional methods had an impact on conducting this study, which aims to ((prepare an educational program using the computer and the method of self-learning and know its impact on the achievement and attitude of students in the subject Elements of Art)).The research sample consisted of first-grade art education students, and the researcher used the experimental design with partial control and prepared an achievement test of the type (multiple choice), and relied on a Likert scale to measure students’ attitudes towards the subject of art elements.